Alienation carried out without respecting the canonical terms - Mróz, Arkadiusz (Prawo Kanoniczne, 2021)
This is the first of two articles presenting the consideration of the canonical and civil-law effectiveness of goods alienation, carried out by ecclesial legal person without meeting the requirements of canon law. The consideration covered in the article constitutes the attempt to find answers to questions of whether the canonical alienation requirements are binding on the secular forum, as well as the question of the effectiveness of alienation carried out without respecting those requirements within the canon law and Polish civil law. This article contains the consideration concerning the alienation of church property, as well as its canonical requirements, the canonization of the civil law regulations concerning the contracts and obligations, as well as canonical effectiveness of alienation carried out without respecting the legal terms. The next article shall present the consideration of the reception of canon law to the Polish legal system, as well as civil-law effectiveness of alienation carried out by ecclesial legal person, without respecting the canonical terms.